ANALISIS KINERJA RANTAI PASOK BERBASIS POHON INDUSTRI UNTUK MENINGKATKAN KEPUASAN PELANGGAN DENGAN METODE SWOT DI PRODUSEN BENIH TANAMAN MANGGA - Muhamad Aef Saefullah (PROCEEDING STIMA)
One of the producers of seeds of Catur Mandiri Tani is a producer of seedlings of existing plants Rajagaluh Kidul Majalengka, must these manufacturers are able to convince consumers with plants that produce, thus making this manufacturer trusted by consumers. However, the growing competition of crop producers in Rajagaluh Kidul, with plant quality almost evenly distributed in every producer in this region, requires that the Catur Mandiri Tani plant producer has a breakthrough in order to have different advantages with other producers. Then by illustrating the supply chain description and getting the propulsion and inhibiting factors present to the producer and allowing it to be analyzed using the SWOT analysis to find and determine the best strategy of the manufacturer. The strategy generated by SWOT analysis is to conduct a new promotional strategy and maximize the available resources available to producers that are capable of producing quality tree seedlings and ultimately able to attract more customers and be able to increase the existing customer satisfaction.